(untitled) (Scholars’ Journal, 2020)
This study explored the academic writing practices in the Nepalese universities and difficulties teachers and students come across in the multilingual context of Nepal. As my study is guided by interpretive paradigm, it demands phenomenological qualitative research design to explore the multiple realities through interviews, documents analysis and focus group discussion. For this, I chose Far Western University, Mid-Western University and Tribhuwan University central campuses as my research site. Two students and two teachers from each of these universities as the study participants were selected with the help of purposive sampling strategy. The participants were interviewed and involved in the focus group discussions and their written documents were analyzed. Thesis writing, translation, book reviews, term paper writing and essay writing were found practised in the universities. Lack of teachers’ own academic writing practices and creation, lack of involvement in professional development activities, lack of much practice in academic paper in classes, lack of motivation and feedback to students in writing, students’ avoidance of writing and poor performance from very beginning, lack of appropriate pedagogy and indifference to academic writing practices and professional development from university administration are the causes of poor performance in academic writing practices in the universities